Adhesive hydrogel as well as preparation method and application thereof in wound dressing
By adding PNIPAM, polyzwitterionic microgels and PDANPs to the hydrogel, the problems of single function and poor mechanical properties of existing hydrogel wound dressings are solved, and efficient wound healing and antibacterial effects are achieved, with excellent biological Compatibility and safety.
Patent Information
- Application Number
- CN202510031177.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing hydrogel wound dressing has a single function and is difficult to have multiple functions such as temperature sensitivity, adhesion, and antibacterial properties. At the same time, the mechanical performance is poor, the cost is high, and the safety is low.
PNIPAM is used as the temperature-sensitive hydrogel matrix material, and polyzwitterionic microgels and polydopamine nanoparticles (PDANPs) are added as fillers to improve the adhesion strength, mechanical strength and antibacterial effect of the hydrogel.
The hydrogel has excellent adhesion, antibacterial properties and mechanical properties, which can pull wound closure and promote wound healing, have good biocompatibility, low cost and high safety.
Smart Images

Figure CN119455084A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a temperature-sensitive hydrogel wound dressing and a preparation method and application thereof. Background Art
[0002] A variety of wound dressings are used to treat wounds, such as gauze, film dressings, foam dressings, hypertonic saline dressings, and hydrogel dressings. Among them, hydrogel dressings are a hot topic in current research, and a variety of hydrogels that promote wound healing have been used in medical practice, such as alginate (Alg), hyaluronic acid (HA), dextran (Dex), chitosan (Chi), etc. These hydrogels have excellent biocompatibility and biodegradability, are non-toxic to the human body, have high water content, and can also absorb tissue fluid exuded from the wound. However, for actual wounds, the above hydrogels have too single functions, and it is of practical significance to develop a multifunctional hydrogel wound dressing.
[0003] Poly(N-isopropylacrylamide) (PNIPAM) is a widely studied thermosensitive polymer with good biocompatibility. The PNIPAM molecular chain contains hydrophobic isopropyl groups and hydrophilic amide groups. When the temperature is higher than its lowest critical solution temperature (LCST~33°C), the hydrophobicity of the isopropyl group takes effect, the distance between the molecular chains becomes smaller, and the polymer exhibits volume shrinkage. When the temperature is lower than its LCST, the volume of the polymer increases after absorbing water. Due to the advantages of PNIPAM's volume phase change behavior at a certain temperature, PNIPAM-based smart hydrogels are widely used in many fields, such as sensors, actuators, wound dressings, etc. When using PNIPAM hydrogel as a wound dressing, in order to fully utilize its thermosensitive phase change characteristics, it is necessary to combine materials with strong adhesion properties to drive wound closure. At present, the main strategy for imparting adhesion properties to PINIPAM is to compound chitosan, polydopamine (PDA) and other substances that can provide adhesion into PINIPAM. However, the adhesion strength that chitosan and PDA can provide is relatively limited, and chitosan has poor mechanical properties. After being added to PNIPAM hydrogel, the mechanical properties of the hydrogel are often reduced. There is also a certain uncertainty in the control of the dosage of PDA, and inappropriate dosage may also reduce the mechanical properties of the hydrogel. The reduction in the mechanical properties of the hydrogel will have an adverse effect on the adhesion strength.
[0004] In addition to adhesion properties, considering that open wounds are susceptible to bacterial infection, researchers will add antibacterial materials to hydrogels to give them antibacterial capabilities. Commonly used antibacterial materials include antibiotics, antimicrobial peptides, and nanomaterials. However, the use of antibiotics can easily lead to drug resistance in microorganisms, making treatment more difficult; the high cost and complex preparation process of antimicrobial peptides limit their application; silver nanoparticles (AgNPs), copper nanoparticles (CuNPs), and metal oxide nanoparticles have all been reported to have good antibacterial capabilities, but the possible cytotoxicity makes them controversial.
[0005] Therefore, providing a wound dressing hydrogel that has multiple functions such as temperature sensitivity, adhesion, antibacterial properties, excellent mechanical properties, low cost and high safety is the key difficulty in current research and development. Summary of the invention
[0006] The purpose of the present invention is to provide an adhesive hydrogel with good application prospects in wound dressings. PNIPAM is used as a thermosensitive hydrogel matrix material, and polyzwitterionic microgels and polydopamine nanoparticles (PDANPs) are added as fillers. Poly(N-isopropylacrylamide) (PNIPAM) is selected as the skeleton of the hydrogel in order to utilize its thermosensitive properties to undergo phase change and volume contraction at human body temperature, thereby pulling the wound to close. The polyzwitterionic microgel improves the adhesion strength of the hydrogel, and the PDA NPs can not only improve the cross-linking density and mechanical strength of the hydrogel, but also the large number of catechol groups on its surface can also improve the adhesion ability of the hydrogel, while giving the hydrogel antioxidant ability. The photothermal response ability of PDANPs also makes the hydrogel show excellent antibacterial effect.
[0007] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows: The present invention provides an adhesive hydrogel, which is prepared from the following raw materials in parts by weight: 2-3 parts of a thermosensitive hydrogel skeleton, 0.1-0.7 parts of a polyzwitterion microgel, and 0-0.02 parts of polydopamine; The thermosensitive hydrogel skeleton is composed of a thermosensitive polymer; and the polyzwitterion microgel is made of polyzwitterions and acrylic acid as raw materials.
[0008] Furthermore, it is prepared from the following raw materials in parts by weight: 2.71 parts of thermosensitive hydrogel skeleton, 0.3 parts of polyzwitterion microgel, and 0.005-0.02 parts of polydopamine.
[0009] Furthermore, it is made from the following raw materials in parts by weight: 2.71 parts of a thermosensitive hydrogel skeleton, 0.3 parts of polyzwitterion microgel, and 0.02 parts of polydopamine; or 2.71 parts of a thermosensitive hydrogel skeleton, 0.3 parts of polyzwitterion microgel, and 0.01 parts of polydopamine; or 2.71 parts of a thermosensitive hydrogel skeleton, 0.3 parts of polyzwitterion microgel, and 0.005 parts of polydopamine.
[0010] Furthermore, the polyzwitterion microgel is a particle with a particle size of 10nm to 100nm, and the polydopamine is a particle with a particle size of 400nm to 600nm.
[0011] Furthermore, the mass ratio of the polyzwitterion to acrylic acid is 1:(0.5-5), preferably 1:(2.5-3.5), and more preferably 1:2.5 or 1:3.5.
[0012] Furthermore, the polyzwitterion is polymethacrylate sulfobetaine.
[0013] Furthermore, the above-mentioned thermosensitive polymer is made of a thermosensitive polymer monomer and a cross-linking agent; the thermosensitive polymer monomer is N-isopropylacrylamide, and the cross-linking agent is N,N'-methylenebisacrylamide; the weight ratio of the thermosensitive polymer monomer to the cross-linking agent is (50~60):1, preferably 53.2:1.
[0014] The present invention also provides a method for preparing the above-mentioned adhesive hydrogel, comprising the following steps: (1) dissolving a thermosensitive polymer monomer, a cross-linking agent, a polyzwitterionic microgel, polydopamine and an initiator in an aqueous solvent to form a mixed solution; (2) Add the catalyst to the mixed solution under inert gas conditions and mix well, then let it stand at room temperature for 20 to 30 hours.
[0015] Furthermore, the aqueous solvent is a PBS solution, the initiator is potassium persulfate, and the catalyst is tetramethylethylenediamine; the usage ratio of the thermosensitive polymer monomer, the aqueous solvent, the initiator and the catalyst is: (0.2~0.3) g: (2~2.5) g: (0.003~0.008) g: (2~10) μL.
[0016] The present invention also provides a double-layer hydrogel, wherein the lower layer is the above-mentioned adhesive hydrogel and the upper layer is a polyzwitterion hydrogel; the polyzwitterion hydrogel is made of a zwitterion monomer and a cross-linking agent.
[0017] Preferably, the polyzwitterionic hydrogel is made of methacrylic acid sulfobetaine and N,N'-methylenebisacrylamide.
[0018] The present invention also provides use of the adhesive hydrogel or double-layer hydrogel in preparing wound dressings.
[0019] Beneficial effects of the present invention: The adhesive hydrogel of the present invention has excellent adhesion, antibacterial and mechanical properties, has the ability to pull wound closure and promote wound healing, and has good biocompatibility; the double-layer hydrogel prepared based on the adhesive hydrogel can also achieve the effect of upper layer anti-fouling and lower layer adhesion, and has great application potential in the field of wound dressings.
[0020] The "thermosensitive polymer" of the present invention refers to a polymer whose volume changes with temperature.
[0021] The "lower layer" in the "double-layer hydrogel" of the present invention refers to the side close to the mold during the film-forming process, and is also the side that adheres to the wound during the application process; the "upper layer" refers to the side close to the air during the film-forming process, and is also the side that does not directly contact the wound during the application process.
[0022] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0023] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the infrared spectrum of the hydrogel, microgel and polydopamine nanoparticles of the present invention.
[0025] Figure 2 a is a graph showing the test results of the adhesion performance of NM1P0, NM3P0, NM5P0, and NM7P0 hydrogels of Comparative Example 1 and Example 1 to pig skin, plastic, glass, aluminum sheet, and cardboard; Figure 2 Where b is NM3P0, NM3P 0.5 , NM3P1 and NM3P2 hydrogel adhesion test results on pig skin, plastic, glass, aluminum sheet and cardboard.
[0026] Figure 3 a is NM3P0, NM3P 0.5 , NM3P1 and NM3P2 hydrogels at 0.5W / cm 2 Temperature variation diagram under near-infrared laser irradiation, Figure 3 b is NM3P0, NM3P 0.5 , NM3P1 and NM3P2 hydrogels at 1W / cm2 Temperature variation diagram under near-infrared laser irradiation; Figure 3 Middle (c) is a diagram showing the temperature change of NM3P1 hydrogel under the photothermal switching cycle state.
[0027] Figure 4 a is NM3P0, NM3P 0.5 , the photothermal antibacterial rate test results of NM3P1 and NM3P2 hydrogels against Escherichia coli; Figure 4 b is NM3P0, NM3P 0.5 , NM3P1 and NM3P2 hydrogels photothermal antibacterial rate test results against Staphylococcus aureus.
[0028] Figure 5 The double-layer hydrogel D-NM3P0, D-NM3P 0.5 , D-NM3P1 and D-NM3P2's adsorption rate test results against Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus).
[0029] Figure 6 The double-layer hydrogel D-NM3P0, D-NM3P 0.5 , D-NM3P1 and D-NM3P2 adsorption rate test results against different concentrations of BCA protein.
[0030] Figure 7 The double-layer hydrogel D-NM3P0, D-NM3P 0.5 , D-NM3P1 and D-NM3P2 antioxidant rate test results.
[0031] Figure 8 The double-layer hydrogel D-NM3P0, D-NM3P 0.5 , hemolysis rate test results of D-NM3P1 and D-NM3P2.
[0032] Fig. 9 This is a test result diagram of the D-NM3P1 hydrogel of the present invention promoting wound healing.
[0033] Fig.10 Figure a is a test result of the expression of wound inflammatory factor IL-4 in the process of promoting wound healing by D-NM3P1 hydrogel of the present invention; Fig.10 Middle b is a test result diagram of the expression of wound inflammatory factor TNF-α in the process of promoting wound healing by D-NM3P1 hydrogel of the present invention; Fig.10 Figure c is a test result of the expression of wound inflammatory factor IL-6 in the process of promoting wound healing by D-NM3P1 hydrogel of the present invention; Fig.10Figure d is a graph showing the test results of the expression of wound inflammatory factor ITGb1 in the process of promoting wound healing by the D-NM3P1 hydrogel of the present invention. DETAILED DESCRIPTION
[0034] The raw materials and equipment used in the embodiments of the present invention are all known products and can be obtained by purchasing commercially available products. As an example, the polydopamine nanoparticles (PDA NPs), polyzwitterion polymethacrylate sulfobetaine (PSBMA) and polyzwitterion microgel of the present invention are prepared by themselves, and the method is as follows: Preparation of PDA NPs: Polydopamine nanoparticles (PDA NPs) are synthesized by the self-polymerization reaction of dopamine in an alkaline environment. 100 mL of deionized water, 40 mL of ethanol, and 2 mL of ammonia water were mixed under magnetic stirring at room temperature, and 0.5 g of dopamine hydrochloride was dissolved in the mixed solution and reacted for 24 hours. The reaction solution was centrifuged and washed three times with deionized water. Finally, the reaction product PDA NPs was collected by freeze drying, and the particle size ranged from 400 nm to 600 nm after scanning electron microscopy.
[0035] Preparation of polyzwitterion PSBMA and microgels: Dissolve 4g sulfobetaine methacrylate (SBMA) and 0.18g NaCl in 30mL deionized water, and pass nitrogen into the mixed solution for 40min, then add 40mg azobisisobutylamidine hydrochloride (AIBA), and react at 70℃ for 12h under nitrogen atmosphere. After the reaction, pour the product into a dialysis bag with a molecular weight cutoff of 3500, replace the dialysis fluid 6 times, and each dialysis time is not less than 6h. After the dialysis is completed, freeze-dry and collect the product PSBMA.
[0036] 26.43g of liquid paraffin, 0.6g of span, and 0.2g of tween were mixed and recorded as mixed solution A. 1g of PSBMA and 0.025g of APS were dissolved in 8.17g of 0.1mol / L LiCl solution, and then 2.5g of acrylic acid (AAc) was added and mixed, which was recorded as mixed solution B. Under the action of mechanical stirring, mixed solution B was slowly added to mixed solution A, and nitrogen was introduced into the mixed system for 20min. After reacting at 60℃ for 4h, centrifuged three times and washed with anhydrous ethanol. Finally, the reaction product microgel was collected by freeze drying, and the particle size ranged from 10nm to 100nm after scanning electron microscopy. It should be noted that the inventors found in previous studies that microgels with better performance can be prepared when the dosage of PSBMA and AAc is within the range of 1: (0.5~5). However, under the ratio of microgel raw materials used in the embodiment of the present invention, the prepared microgel particles have a relatively better improvement in the adhesion performance of hydrogels. However, this preparation ratio is only an example and does not serve as a special restriction on the specific dosage of microgel raw materials.
[0037] Example 1. Preparation of the adhesive monolayer hydrogel of the present invention 0.266g N-isopropylacrylamide (NIPAM) was dissolved in 2.334g 0.01M PBS solution, and 0.005g N,N'-methylenebisacrylamide (MBAA), 0.005g potassium persulfate (KPS), and a certain amount (amounts shown in Table 1) of PDANPs and microgels were added to the system. After dissolution, nitrogen was passed through the mixed solution for 5 minutes, and then 2~10 μL of catalyst tetramethylethylenediamine (TEMED) was added. The adhesive monolayer hydrogel was placed in the mold at room temperature for 24 hours. Each group of monolayer hydrogels was named NM1P0, NM3P0, NM5P0, NM7P0, NM3P0, NM4P0, NM5P0, NM6P0, NM7P0, NM8P0, NM9P0, NM10P0, NM11P0, NM12P0, NM13P0, NM14P0, NM15P0, NM16P0, NM17P0, NM18P0, NM19P0, NM20P0, NM21P0, NM22P0, NM23P0, NM24P0, NM25P0, NM26P0, NM27P0, NM28P0, NM29P0, NM30P0, NM31P0, NM32P0, NM34P0, NM35P0, NM36P0, NM37P0, NM38P0, NM39P0, NM40P0, NM5 0.5 , NM3P1 and NM3P2.
[0038] Table 1: Example 2: Preparation of the double-layer hydrogel of the present invention Take the adhesive hydrogel NM3P0, NM3P 0.5 , NM3P1 and NM3P2, 0.3 g SBMA, 0.003 g MBAA, and 0.003 g photoinitiator (Irgacure 2959) were dissolved in 1.7 g 0.01 M PBS solution to obtain a mixed solution, which was added to the surface of the adhesive hydrogel and polymerized by ultraviolet light to prepare double-layer hydrogels D-NM3P0 and D-NM3P 0.5 , D-NM3P1 and D-NM3P2.
[0039] Comparative Example 1: Preparation of hydrogel NM0P0 0.266g N-isopropylacrylamide (NIPAM) was dissolved in 2.334g 0.01M PBS solution, and 0.005g N,N'-methylenebisacrylamide (MBAA) and 0.005g potassium persulfate (KPS) were added to the system. After dissolution, nitrogen was passed into the mixed solution for 5 minutes, and then 2~10 μL of catalyst tetramethylethylenediamine (TEMED) was added. The mixture was placed at room temperature for 24 hours to obtain the pure PNIPAM-based hydrogel NM0P0.
[0040] Comparative Example 2: Preparation of hydrogel with only PDA NPs added Refer to NM3P in Example 1 0.5 , NM3P1 and NM3P2 preparation methods, only the amount of microgel was adjusted to 0, and the hydrogel NM0P was prepared by adding only polydopamine nanoparticles 0.5 , NM0P1 and NM0P2. The adhesion performance test showed that doping with PDA NPs alone did not significantly enhance the adhesion The beneficial effects of the present invention are demonstrated by experimental examples. The characterization method involved in the present invention is as follows: 1. Structural and morphological analysis FT-IR spectroscopy (Bruker Tensor-27 spectrometer) was used to characterize the chemical structure of the monolayer hydrogels, with microgels and PDA NPs as control samples.
[0041] 2. Adhesion performance The adhesion of the single-layer hydrogel to different materials was evaluated by lap shear test. The fat layer on the fresh pig skin was removed, the surface grease was washed off with detergent, and it was cut into strips of 100mm (length) × 25mm (width). Aluminum sheets, plastics, cardboard and glass of the same size were prepared. The 25mm (length) × 25mm (width) × 1mm (thickness) hydrogel and the hydrogel of comparative example 1 were sandwiched between the above five substrates, and the tensile test was performed at room temperature for 5 minutes. At room temperature, the tensile test was performed using a universal testing machine (CMT-6104, MITS) with a tensile rate of 10mm / min. Each sample was tested three times.
[0042] 2. Photothermal performance evaluation The single-layer hydrogel was prepared into a cylinder with a diameter of 1 cm and a height of 1 cm. The hydrogel was irradiated from a height of 20 cm using a near-infrared laser (NIR) with a wavelength of 808 nm and a power of 0.50 W / cm 2 and 1.00W / cm 2Two different powers were tested. An infrared thermal imager (UTI120S) was used to record the surface temperature of the hydrogel at different exposure times of near-infrared light. The power was selected to be 1.00W / cm 2 A photothermal cycle test was performed. When the surface temperature of the hydrogel reached a peak under the action of near-infrared light, the laser emitter was turned off to allow the hydrogel to cool at room temperature. The cycle was repeated three times.
[0043] 3. Photothermal antibacterial performance Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were used to perform photothermal antibacterial tests on single-layer hydrogels. The prepared hydrogel samples were sterilized under ultraviolet light, and the front and back sides of the hydrogels were irradiated for 10 hours. 100 μL of bacterial suspension (10 7 CFU / mL) were applied on the surface of the hydrogel, and one group was illuminated by near-infrared laser (808 nm, 1.00 W / cm 2 ) was irradiated at a height of 20 cm from the sample for 5 minutes, and the other group was not irradiated with near-infrared light. Then 900 μL PBS solution was added to resuspend the surviving bacteria on the hydrogel surface, and the bacterial suspension was diluted to 10 5 CFU / mL. Take 100 μL of the diluted bacterial suspension for plate count. In addition, take 100 μL of the bacterial suspension (10 7 CFU / mL) were placed in a centrifuge tube and performed the same operation as above as a negative control group.
[0044] 4. Bacterial surface adhesion 10 μL of a concentration of 10 7 CFU / mL of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) suspensions were added to the double-layer hydrogels and incubated at 37°C for 1 hour. After the incubation, the hydrogels were gently washed five times with PBS solution to remove loose bacteria on the surface. Then, the double-layer hydrogels were soaked in 1 mL of PBS solution and ultrasonically vibrated for 1 hour, and the solution was diluted to 10 5 CFU / mL, take 100 μL of the diluted bacterial suspension for plate count. Use the same diluted original bacterial suspension as the control group.
[0045] 5. Protein adsorption test Using bovine serum albumin (BCA) as a model protein, the antifouling performance of the double-layer hydrogel was tested by protein adsorption experiments. 200 μL of bovine serum albumin solution with a concentration of 250, 500 or 1000 μg / mL was added to the hydrogel samples, and after incubation at 37°C for 30 minutes, 20 μL of the solution was taken out from each well, and 200 μL of BCA working solution was added. After waiting for 30 minutes, the absorbance of the solution in the standard well and the sample well was measured with an ELISA reader.
[0046] 6. Antioxidant test The antioxidant capacity of the material was evaluated using a total antioxidant capacity detection kit. The double-layer hydrogel sample was immersed in ABTS solution and incubated at 37°C for 30 minutes, and the absorbance was measured at 735 nm using a microplate reader.
[0047] 7. In vitro hemolysis test The rat blood was centrifuged at 1500rpm for 10min, the supernatant was discarded, and the red blood cells were diluted tenfold with normal saline to form a red blood cell suspension. The experimental group added a double-layer hydrogel, 100μL red blood cell suspension and 900μL normal saline, the negative control group added 100μL red blood cell suspension and 900μL normal saline, and the positive control group added 100μL red blood cell suspension and 900μL double distilled water. After incubation at 37℃ for 1h, the material was removed, centrifuged at 2000rpm for 10min, the supernatant was taken into a 96-well plate, and the absorbance was measured at 540nm with an ELISA reader.
[0048] 8. Cytotoxicity test The cytotoxicity of the double-layer hydrogel was tested on L929 mouse fibroblasts using the CCK-8 kit. The hydrogel was soaked in 75% ethanol for 24 hours and sterilized by ultraviolet irradiation for 1 hour. The sample was then rinsed 5 times with PBS to remove the residual ethanol, and then placed in a 24-well plate and soaked in 1mL of complete DMEM medium. The plate without the sample was used as the control group, and the well plate was placed in a constant temperature incubator for 72 hours to prepare the extract. At the same time, L929 cells were seeded into a 96-well plate at a density of 5000 cells / well. After the cells grew for 24 hours, the old culture medium was discarded and replaced with 200μL / well of the extract. L929 cells were cultured in the extract for 24 hours and 72 hours. After the incubation, the extract was replaced with 100μL of DMEM medium containing 10% CCK-8 reagent, and after incubation at 37°C for 1 hour, the absorbance was measured at 450nm using an enzyme reader.
[0049] 9. Wound healing test Male SD rats were anesthetized, the back hair was shaved, and a full-thickness skin defect model was established on the back. After the wound was treated with D-NM3P1 hydrogel or PBS, half of the wounds were irradiated with NIR laser and the other half were not. The wound sites were photographed on days 0, 3, 7, and 14, and the wound closure rate was calculated. On day 14, cytokine determination was performed after sampling.
[0050] Experimental Example 1: Characterization results of hydrogel structure of the present invention like Figure 1 As shown in the FTIR spectrum, 3434 cm -1There is an obvious absorption peak at 3311 cm -1 The absorption peak at 2965 cm corresponds to -NH stretching vibration. -1 The absorption peak at 1172 cm -1 The absorption peak at 1643 cm -1 The absorption peak at corresponds to the C=O stretching vibration, which proves the successful synthesis of the hydrogel of the present invention.
[0051] Experimental Example 2: Adhesion performance test results of the hydrogel of the present invention The results of the test on five substrates including pigskin, plastic, glass, aluminum sheet and cardboard are as follows: Figure 2 As shown. The pure PNIPAM hydrogel NM0P0 of Comparative Example 1 showed almost no adhesion; while in the hydrogel without adding PDA NPs, with the increase of the amount of microgel added, the adhesion ability of the hydrogel showed a trend of first increasing and then decreasing, among which NM3P0 showed the best adhesion ( Figure 2 After adding PDA NPs, the large amount of catechol groups in PDA NPs further improved the mechanical strength and adhesion strength of NMP hydrogel. Therefore, with the increase of PDA NPs content, the adhesion strength of hydrogel increases successively ( Figure 2 (b)
[0052] Experimental Example 3: Test results of the photothermal properties of the hydrogel of the present invention After NIR laser irradiation of the hydrogel, NM3P 0.5 The temperatures of NM3P1 and NM3P2 rose rapidly, and the temperature of NM3P0 also rose under long-term NIR laser irradiation. Under NIR laser irradiation, the rate of temperature increase of the hydrogel increased with the increase of PDANPs content. In addition, changing the power density of NIR laser can adjust the photothermal conversion rate of hydrogel. When the power density was increased from 0.5W / cm 2 ( Figure 3 a) Increase to 1W / cm 2 ( Figure 3 In b), the stable temperature of NM3P1 increases from 42°C to 68°C, which shows that the photothermal properties of the hydrogel of the present invention can be adjusted, and NM3P 0.5 , the stable temperature of NM3P1 under higher density NIR laser irradiation is more suitable for contact with the skin. Taking into account the mechanical properties, adhesion properties and photothermal density test results, NM3P1 is the sample with the best performance. Further evaluation of its photothermal stability through laser switching cycles found that after three laser switching cycles, the stable temperature of NM3P1 is relatively stable ( Figure 3(c) shows that the hydrogel of the present invention has good photothermal stability and can be used for photothermal antibacterial treatment.
[0053] Experimental Example 4: Test results of the photothermal antibacterial properties of the hydrogel of the present invention The photothermal antibacterial test was carried out using Escherichia coli and Staphylococcus aureus as models. The results are as follows Figure 4 As shown. Without NIR laser irradiation, the control group and the experimental group had almost no bactericidal ability. After NIR laser irradiation, the control group and NM3P0 showed almost no bactericidal ability because they could not perform photothermal conversion. However, the hydrogel with PDA NPs quickly heated up under NIR laser irradiation, showing good bactericidal ability. The bactericidal rate of NM3P1 against Escherichia coli was 99.96%, and the bactericidal rate against Staphylococcus aureus was 99.97%.
[0054] Experimental Example 5: Anti-adsorption test results of the double-layer hydrogel of the present invention Using Escherichia coli and Staphylococcus aureus as models, the ability of the double-layer hydrogel to prevent bacterial adsorption was tested. Figure 5 As shown, the removal rates of the double-layer hydrogel of the present invention for Escherichia coli and Staphylococcus aureus are both over 99%.
[0055] Using BCA protein as a model, the ability of the double-layer hydrogel to prevent protein adsorption was tested. Figure 6 As shown in the figure, when the protein concentration is low (250 μg / mL), the protein removal rate of the double-layer hydrogel of the present invention is above 99%; for 500 μg / mL protein solution, the removal rate is above 98%; when the protein concentration is high (1000 μg / mL), the removal rate can also reach 95%.
[0056] Experimental Example 6: Test results of the antioxidant properties of the double-layer hydrogel of the present invention The antioxidant capacity of D-NMP hydrogel was determined by the ABTS method. Figure 7 As shown in Figure 2, D-NM3P0 without PDA NPs had almost no ability to scavenge reactive oxygen species, while D-NM3P 0.5 , D-NM3P1 and D-NM3P2 all had an ROS scavenging capacity of about 50%.
[0057] Experimental Example 7, Blood Compatibility Test Results of the Double-layer Hydrogel of the Present Invention The blood compatibility of the hydrogel of the present invention was evaluated by hemolysis test. Figure 8 As shown. D-NM3P0, D-NM3P 0.5 The hemolysis rates of D-NM3P1, D-NM3P2 were 2.39%, 1.22%, 1.75% and 3.54%, respectively, all below 5%, showing good blood compatibility.
[0058] Experimental Example 7: Test results of wound treatment with double-layer hydrogel of the present invention The results are as follows Fig. 9 As shown, the wound was treated with D-NM3P1 hydrogel combined with NIR, and the wound closure rate on the third day was significantly higher than that of other control groups and experimental groups. On the fourteenth day, the healing rate of the D-NM3P1+NIR group was the highest, and the wound was completely closed.
[0059] Further characterization of wound inflammation revealed Fig.10 As shown. In the wound tissue of the D-NM3P1+NIR group, inflammatory factors such as TNF-α and IL-6 were reduced, and IL-4 expression increased, indicating that the wound healing effect of the D-NM3P1+NIR group was better. The D-NM3P1+NIR group also expressed more integrin β1 (ITGb1). Integrin β1 is part of the cell surface receptor and is involved in the interaction between cells and the extracellular matrix (ECM). In the process of wound healing and tissue reconstruction, integrin β1 is essential for cell adhesion, migration and reconstruction of the extracellular matrix. During the experiment, the D-NM3P1 hydrogel was irradiated with NIR to heat up and shrink, thereby driving the tissue closure. In this process, the hydrogel provided a tensile force in the direction of wound healing. The force signal activated the mechanical sensitive signaling pathways in the cells (such as focal adhesion kinase, FAK, or Rho family GTPase, etc.), thereby upregulating the expression of integrin β1. The increase in integrin β1 helps to enhance the adhesion ability of cells to the matrix and promote the migration of fibroblasts, epithelial cells, etc., thereby promoting tissue repair and healing.
[0060] In summary, the adhesive hydrogel prepared by the present invention has excellent adhesion, antibacterial and mechanical properties, has the ability to pull wound closure and promote wound healing, and has good biocompatibility; the double-layer hydrogel prepared based on the adhesive hydrogel can also achieve the effect of upper layer anti-fouling and lower layer adhesion, and has great application potential in the field of wound dressings.
Claims
1. An adhesive hydrogel, characterized in that: The method is prepared from the following raw materials in parts by weight: 2-3 parts of thermosensitive hydrogel skeleton, 0.1-0.7 parts of polyzwitterion microgel, and 0-0.02 parts of polydopamine; The thermosensitive hydrogel skeleton is composed of a thermosensitive polymer; and the polyzwitterion microgel is made of polyzwitterions and acrylic acid as raw materials.
2. The adhesive hydrogel according to claim 1, characterized in that The invention is prepared from the following raw materials in parts by weight: 2.71 parts of a thermosensitive hydrogel skeleton, 0.3 parts of polyzwitterion microgel, and 0.005-0.02 parts of polydopamine.
3. The adhesive hydrogel according to claim 1 or 2, characterized in that The polyzwitterion microgel is a particle with a particle size of 10nm to 100nm; the polydopamine is a particle with a particle size of 400nm to 600nm.
4. The adhesive hydrogel according to claim 1 or 2, characterized in that The mass ratio of the polyzwitterion to acrylic acid is 1:(0.5-5).
5. The adhesive hydrogel according to claim 1 or 2, characterized in that The polyzwitterion is polymethacrylate sulfobetaine.
6. The adhesive hydrogel according to claim 1 or 2, characterized in that The thermosensitive polymer is made of a thermosensitive polymer monomer and a crosslinking agent; the thermosensitive polymer monomer is N-isopropyl acrylamide, and the crosslinking agent is N,N'-methylenebisacrylamide; the weight ratio of the thermosensitive polymer monomer to the crosslinking agent is (50-60):
1.
7. The method for preparing the adhesive hydrogel according to any one of claims 1 to 6, characterized in that: The steps include: (1) dissolving a thermosensitive polymer monomer, a cross-linking agent, a polyzwitterionic microgel, polydopamine and an initiator in an aqueous solvent to form a mixed solution; (2) Add the catalyst to the mixed solution under inert gas conditions and mix well, then let it stand at room temperature for 20 to 30 hours.
8. The preparation method according to claim 7, characterized in that: The aqueous solvent is PBS solution, the initiator is potassium persulfate, and the catalyst is tetramethylethylenediamine; the usage ratio of the temperature-sensitive polymer monomer, the aqueous solvent, the initiator and the catalyst is: (0.2~0.3) g: (2~2.5) g: (0.003~0.008) g: (2~10) μL.
9. A double-layer hydrogel, characterized in that: The lower layer is the hydrogel according to any one of claims 1 to 6, and the upper layer is a polyzwitterionic hydrogel; the polyzwitterionic hydrogel is made of zwitterionic monomers and a crosslinking agent.
10. Use of the adhesive hydrogel according to any one of claims 1 to 6 or the double-layer hydrogel according to claim 9 in preparing wound dressings.
Citation Information
Patent Citations
Tri-dopamine based compound and polymer as well as preparation method and application thereof
CN107686541A
Biomaterial modified with hydrophilic lubrication coating on surface and preparation method of biomaterial
CN109912826A
Antifouling-sterilization-release multifunctional response antibacterial surface and preparation method thereof
CN112048223A
Salt-sensitive photo-thermal gel as well as preparation and application thereof
CN114605591A
Surfaces comprising attached quorum sensing modulators
US20180125066A1